Mapping the Landscape of Technology-Enhanced Misconception Research in Science Education: Trends, Impact, and Future Directions - Oktova, Raden; Sukarelawan, Moh. Irma (Universitas Ahmad Dahlan, 2025)
This study uses a quantitative bibliometric approach to map trends, collaborations, and research directions in the field of technology-based misconception remediation in science education. Data were extracted from the Scopus database using keyword searches related to misconceptions, educational technology, and science learning from 2000 to 2024. After filtering, 280 documents were analyzed using VOSviewer to explore publication patterns, author collaboration networks, and conceptual connections through co-authorship, co-word, and co-citation analysis. Network map visualizations provide an overview of key actors, popular topics, and emerging thematic clusters. The study results indicate significant growth in publications and international collaboration, while also identifying potential research gaps. These findings are expected to serve as a strategic reference for researchers and policymakers in directing technology-based pedagogical research and innovation to address misconceptions in science education.